Theory of Mind Development in School-Aged Left-Behind Children in Rural China - Liu, Yanchun; Yang, Xuelian; Li, Jingjing; Kou, Erhu; Tian, Huidong; Huang, Heqing (Frontiers in Psychology, 2018)
The current study aimed to investigate differences in theory of mind between left-behind children and non-left-behind children in rural China and to examine the potential protective role of general reasoning ability in left-behind children’s theory of mind. Participants included 213 children aged 7.10–13.67 years (111 boys and 102 girls, M = 10.51 years, SD = 1.33), 101 of whom were left behind in rural areas by one or both migrating parents for at least 6 months. The Strange Stories task, a second-order false belief task, and a faux pas task were used to measure children’s theory of mind, and Sessions B and C in Raven’s Standard Progressive Matrices were used to test children’s general reasoning ability. The results showed that left-behind children scored lower on both the faux pas task and Strange Stories task. Additionally, on second-order false belief understanding, left-behind boys performed worse than non-left-behind boys, while left-behind girls scored higher than non-left behind girls. Moreover, children’s general reasoning ability moderated the relationship between parental migrant status and children’s faux pas understanding: For children with high levels of general reasoning ability, left-behind children performed similarly to non-left-behind children, while for children with low levels of general reasoning ability, left-behind children scored lower than non-left-behind children, indicating that general reasoning ability buffered the negative effect of being left behind on children’s theory of mind development. The implications of these findings for training directed at left-behind children are discussed.